Ghost knight - Funke, Cornelia, 1958- (Little, Brown, 2012)
Eleven-year-old Jon Whitcroft and new friend Ella summon the ghost of Sir William Longspee, who may be able to protect Jon from a group of ghosts that threatens him harm from the day he arrives at Salisbury Cathedral's boarding school. Includes historical notes.